Manajemen Zakat di BAZ Kabupaten Lumajang: Zakat Management at BAZ Lumajang Regency - Nikmatul Masruroh (Fenomena, 2013)
The efforts of BAZ and LAZ to encourage zakat payers to disburse their funds require creativity and innovation in management policies, especially to become policies considered as best practices. Therefore, policies deemed as best practices need to be taken, analyzed, and evaluated to serve as benchmarking. Currently, searching for best practices policies of an institution is a necessity, including in zakat management. BAZ Lumajang Regency has shown the highest fund graph in East Java for several years, even though this region does not have a constitutional instrument in the form of a Zakat Regional Regulation. Moreover, Lumajang's demography is not unique in terms of Islamic atmosphere compared to other regions in East Java. From this illustration, it can be concluded that there are best practices policies at BAZ Lumajang Regency, so that zakat management benchmarking from BAZ Lumajang Regency can be expected. Upaya BAZ dan LAZ dalam mendorong wajib zakat untuk menyalurkan dananya membutuhkan kreativitas dan inovasi dalam kebijakan manajemen, terutama untuk menjadi kebijakan yang dianggap sebagai best practices. Oleh karena itu, kebijakan yang dinilai sebagai best practices perlu diambil, dianalisis, dan dievaluasi untuk dijadikan benchmarking. Saat ini, pencarian kebijakan best practices suatu institusi menjadi suatu keharusan, termasuk dalam pengelolaan zakat. BAZ Kabupaten Lumajang telah menunjukkan grafik dana tertinggi di Jawa Timur selama beberapa tahun, meskipun daerah ini tidak memiliki instrumen konstitusi berupa PERDA Zakat. Selain itu, demografi Lumajang tidak unik dalam hal atmosfer keislaman dibandingkan daerah lain di Jawa Timur. Dari gambaran ini, dapat disimpulkan bahwa terdapat kebijakan best practices di BAZ Kabupaten Lumajang, sehingga dapat diharapkan adanya benchmarking manajemen zakat dari BAZ Kabupaten Lumajang.